FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KANTOR SAMSAT KOTA PRAYA - M. Wahyullah; Febriantina Istiharoh; Ida Ayu Nursanty (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2024)
This research aims to determine the factors that influence motorbike taxpayer compliance at the Praya City Samsat Office. This type of research uses quantitative methods with an associative approach and collects primary data using questionnaire techniques which are measured using a Likert scale. The population in this study were taxpayers registered at the Praya City Samsat Office, totaling 194,926. Sampling used the Slovin technique. The sample used was 100 respondents. The data analysis technique used is multiple linear regression analysis with IBM SPSS 25 software. The results of this study show that taxpayer awareness (X1), tax service quality (X3), moral obligations (X4) do not have a positive effect on motor vehicle taxpayer compliance in Praya City Samsat Office, while tax knowledge (X2) and tax sanctions (X5) have a positive effect on motor vehicle taxpayer compliance at the Praya City Samsat Office. The R Square figure shows a value of 68.2% so that 31.8% is influenced by other variables.